Risikofaktoren für altersabhängige Makuladegeneration: Wie ist die aktuelle Datenlage? : Leitthema - Brandl, Caroline; Heid, Iris M.; Helbig, H.; Holz, Frank G.; Finger, Robert P.; Mauschitz, Matthias M. (Die Ophthalmologie, 2025)
Background Identifying risk factors for age-related macular degeneration (AMD) is crucial for patient counseling and the development of potential prevention strategies. Objectives This study summarizes the current epidemiological evidence on AMD risk factors, analyzes their clinical relevance, and discusses potential preventive measures. Materials and methods A systematic literature review was conducted to assess demographic, genetic, and modifiable risk factors for AMD, including smoking, diet, and physical activity. Results Age is the strongest risk factor for early and advanced AMD. Genetic predisposition also plays a critical role, particularly from genetic variants in the complement and lipid metabolism pathways and extracellular matrix. Modifiable factors such as smoking, dietary habits, and physical activity significantly influence the risk of AMD. Recent studies further suggest a potentially beneficial effect of medication intake, such as metformin and statins. Conclusion Epidemiological data indicate that smoking cessation, adherence to a Mediterranean diet, and regular physical activity are associated with a reduced risk of AMD over time. These factors should be integral to patient counseling. The continued extension of longitudinal study data will be key to refining individual risk profiles and optimizing prevention strategies.
Online publiziert: 13. Juni 2025
Gesehen am 28.08.2025